GULAM MEMMEDLI AND HIS TEZKIRE - Halide Gamze İnce YAKAR (Fırat University, 2019)
On 15 June 1954, Azerbaijan Academy of Sciences admitted Gulam Memmedli’s comprising six files for the Manuscripts Section of the Literature Institute. This six-file tezkire has been translated into Modern Turkish and systematically investigated by the researcher. The tezkire, donated to the Manuscripts Section of the Literature Institute in the name of Nizami, is not bound, consisting of separate sheets, and faulty in its organization, i.e., prepared with disregard of the tezkire conventions, having no introduction, nor an epilogue, and irrespective of any chronological order. The manuscript version of the work contains 1466 pages, with 1418 pages for the body text, and 48 pages for the list of sources and an index. Among the Azerbaijani intellectuals sent to Iran by the Soviet army was Gulam Memmedli, born in Tabriz, in 1897. A large part of the tezkire was written during this period, between 1940-46, when the author was in Iran. Therefore, a considerable amount of information and details regarding Iranian history and Southern poets can be found in the tezkire. In the present study, some place is devoted to such poets as M. A. Möcüz and Heyran Hanım, some of the outstanding figures of the world of literature and culture of that period, their works and influences. Such books of the author as the Settar Han Anthology of Poetry and An Anthology of Southern Azerbaijani Poets were published following his research in Tabriz. Gulam Memmedli has had significant contributions to Turkish language and literature in respect of several manuscripts taken out of personal collections, completion of the missing sections through comparison, and their publication.